Solution:
Given the sequence;
![-3,6,-12,24](https://img.qammunity.org/2023/formulas/mathematics/high-school/55d16hrp5z3gj6ziox15w88q8kct693d7p.png)
The common ratio is the ratio between two consecutive numbers in a geometric sequence.
Thus;
![\begin{gathered} r=(a_2)/(a_1)=(a_3)/(a_2) \\ \\ r=(6)/(-3) \\ \\ r=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ykxtba1jxsgjx1nvp4h7lu5oamrqkysfaw.png)
Common Ratio:
![r=-2](https://img.qammunity.org/2023/formulas/advanced-placement-ap/college/up6vn85pjnqfxh1mrxl7ke2yhkhpq399wv.png)
Also, given the formula;
![a_n=-3\cdot(-2)^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/9s4x61oh07d4nd0s1zmfjvsqvsql7re6rw.png)
The formula is an explicit formula of the geometric sequence.
The recursive formula is;
![\begin{gathered} a_n=r(a_(n-1)) \\ \\ a_n=-2(a_(n-1)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3lcu96wv1p098y6mxmgc8ujzemhhb1yv2w.png)
Then, the ninth term is;
![\begin{gathered} n=9 \\ \\ a_9=-3\cdot(-2)^(9-1) \\ \\ a_9=-3\cdot(-2)^8 \\ \\ a_9=-3(256) \\ \\ a_9=-768 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/c5yohz3sxlj8p7w7vh75kaexui5jdjyewx.png)
The ninth term is;
![a_9=-768](https://img.qammunity.org/2023/formulas/mathematics/high-school/y8cicxekv27pjlzf9f2oar8shq3ncx4yns.png)